Dilema Pidana Mati Bersyarat Antara Kepastian Hukum dan Fenomena Deret Tunggu Kematian - Lim, Arron Jonatan; Siregar, Elizabeth; Wahyudhi, Dheny (PAMPAS: Journal of Criminal Law, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code marks a paradigm shift in Indonesia's sentencing system by introducing a conditional death penalty through a 10-year probationary period. This policy is intended as a middle ground between retributive and rehabilitative justice. However, this research argues that such judicial innovation triggers new legal problems due to the normative ambiguity in Article 100 of the Criminal Code, specifically regarding the criteria for "commendable attitude and actions" which lack objective parameters. Utilizing normative legal research with statutory and conceptual approaches, the results indicate that the absence of measurable indicators creates extreme legal uncertainty and poses a risk of administrative abuse of discretion. This condition further exacerbates the death Row Phenomenon, which contradicts humanitarian principles. Furthermore, the author criticizes the absence of integrated restitution for victims as a commutation requirement, suggesting that the spirit of restorative justice in the new Criminal Code has not been substantively achieved. This study concludes the urgent need for implementing regulations containing quantitative assessment indicators and the establishment of an independent multidisciplinary body to ensure evaluation transparency. Strengthening the restitution aspect must be a primary pillar to achieve a sentencing system that is truly fair and balanced for all parties ABSTRAK Pengesahan Undang-Undang Nomor 1 Tahun 2023 tentang KUHP menandai pergeseran paradigma pemidanaan di Indonesia dengan memperkenalkan pidana mati bersyarat melalui masa percobaan 10 tahun. Kebijakan ini dimaksudkan sebagai jalan tengah antara keadilan retributif dan rehabilitatif. Namun, penelitian ini berargumen bahwa inovasi yuridis tersebut justru memicu problematika baru akibat kekaburan norma pada Pasal 100 KUHP, khususnya mengenai kriteria "sikap dan perbuatan terpuji" yang tidak memiliki parameter objektif. Menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual, hasil studi menunjukkan bahwa ketiadaan indikator terukur menciptakan ketidakpastian hukum yang ekstrem dan berisiko pada penyalahgunaan diskresi administratif. Kondisi ini juga memperburuk fenomena deret tunggu kematian (Death Row Phenomenon) yang bertentangan dengan prinsip kemanusiaan. Lebih lanjut, penulis mengkritik absennya integrasi restitusi bagi korban sebagai syarat komutasi, sehingga semangat keadilan restoratif dalam KUHP baru belum tercapai secara substantif. Penelitian ini menyimpulkan perlunya peraturan pelaksana yang memuat indikator penilaian kuantitatif serta pembentukan lembaga independen multidisipliner untuk menjamin transparansi evaluasi. Penguatan aspek restitusi harus dijadikan pilar utama guna mewujudkan sistem pemidanaan yang benar-benar adil dan seimbang bagi seluruh pihak.